Polarity effects, resistance, and probiotic enhancement of intoxication of Salmonella enterica fraB mutants in murine models - Anice Sabag-Daigle; Erin F. Boulanger; Maryam Baniasad; Yongseok Kim; Madalyn Moore; Bailyn Hogue; Andrew Schwieters; Venkat Gopalan; Vicki Wysocki; Brian M. M. Ahmer (PLoS ONE, 2025)
FraB is a deglycase in a metabolic pathway that allows Salmonella to utilize fructose-asparagine (F-Asn). Some fraB mutants are sensitive to F-Asn due to the accumulation of 6-phosphofructose-aspartate (6-P-F-Asp), a toxic intermediate in this pathway. We determined that different alleles of fraB cause different amounts of 6-P-F-Asp-mediated toxicity due to effects on the expression of the downstream gene, fraD , a kinase. Mutations in fraD or fraA (a transporter) cause resistance to F-Asn intoxication, and these mutations occur during infection. To better mimic the effect of a hypothetical FraB inhibitor in mouse models, we characterized a non-polar mutant encoding a catalytically inactive FraB (FraB E214A). We also compared a typical mouse chow and a high-fat chow and found that the latter decreases the variation in colonization typically observed during infection of CBA/J mice with Salmonella . Because the high-fat chow lacks F-Asn, the fraB E214A mutant was not attenuated in mice fed this diet unless F-Asn was supplemented. F-Asn supplementation resulted in a 100-fold reduction of colony forming units (CFU) recovered from feces compared to wild-type. Co-infection of Salmonella with a Salmonella “probiotic” strain that is neither virulent nor capable of consuming F-Asn (a SPI1 SPI2 fraR-BDAE ansB mutant) led to a dramatic 10,000-fold reduction in CFU and a 1000-fold reduction in lipocalin-2, a proxy marker of inflammation. This probiotic strain presumably competes for nutrients other than F-Asn, driving the fraB mutant to consume a higher proportion of F-Asn and greater 6-P-F-Asp intoxication. Thus, a putative inhibitor of FraB, when administered with F-Asn and a probiotic, may provide a new therapeutic strategy for treating Salmonella gastroenteritis.